Cyano-containing tetraphenylethene isomers: similar bright mechanoluminescence, but diverse recoverable processes. (23rd November 2020) - Jiang, Yuqing; Chang, Xiaoyong; Xie, Weiwei; Huang, Guangxi; Li, Bing Shi
Abstract : Cyano-substituted tetraphenylethene derivatives demonstrated cyclic utilization of bright mechanoluminescence, an irreversible structural transition between polymorphs and thermochromism. Abstract : Two simple luminogens p -CN and m -CN were obtained by introducing a cyano group at the para - and meta - position of the tetraphenylethene (TPE) skeleton, respectively. The two luminogens exhibited bright blue mechanoluminescence (ML) even under subdued light both in their crystalline and as-prepared powder state. They realized in situ recovery of ML with a simple thermal treatment, but with diverse recovery processes: p -CN returned to its original blue fluorescence, while m -CN transformed into cyan fluorescence. Molecule p -CN crystallized into a single crystal p -CN-c with blue emission, while m -CN crystallized into two polymorphs, m -CN-c1 and m -CN-c2, with blue emission and cyan emission, respectively. Crystallography analysis suggested that their ML was due to the interlocked molecular packing and intact three-dimensional supramolecular networks stabilized by the multiple strong intermolecular interactions. Their diverse recovery processes upon thermal stimuli were ascribed to their different transition path between their polymorphs. p -CN returned to molecular packing similar to its single crystal, while m -CN irreversibly transformed from packing similar to crystal m -CN-c1 into that of m -CN-c2, which had lower energy and a more twisted conformation. These results provide an important insight for better deciphering the relationship between ML and molecular packing, and help to optimize the rational molecular design of ML materials.